The Efficacy of Teaching Methods that Grade 10 English First Additional Language Teachers Use, and the Challenges to Teach Poetry - Motlhaka, Hlaviso; Sekete, Kgaugelo (Universitas Jambi, Magister Program of English Education Department, 2025)
Teaching poetry presents significant challenges for many teachers, often leaving learners struggling to grasp its complexities. In some schools, poetry is even phased out due to poor learner performance. This study investigated the effectiveness of methods used by Grade 10 English First Additional Language teachers to teach poetry. A qualitative approach was adopted, with a case study design. Two teachers were purposefully sampled, and data was collected through lesson observations and semi-structured interviews. Observation data was analysed using content analysis, while interview data was examined through thematic analysis.The findings reveal several challenges: learners’ lack of interest in poetry, difficulties in explaining figurative language, fear of misinterpretation, limited English vocabulary, inadequate access to diverse poetry texts, overcrowded classrooms, time constraints, and insufficient teacher training and confidence. Teachers mainly used read-aloud and recitation methods to model pronunciation, rhythm, and intonation. These approaches gave learners opportunities to practice speaking English fluently but limited their engagement. Consequently, learner participation remained low, with few opportunities for critical thinking, personal interpretation, or emotional connection. Learners perceived poetry as abstract, irrelevant, and boring, which further reduced their willingness to participate. The study recommends adopting interactive and learner-centred strategies to address these challenges. These include discussion-based learning, dramatization, role-playing, group work, peer teaching, and question-and-answer techniques. Furthermore, integrating ICT tools—such as YouTube performances, recorded recitals, and animated poetry—can enhance learner engagement, comprehension, and confidence. By diversifying teaching approaches, teachers can foster creativity, encourage multiple interpretations, and make poetry more meaningful and accessible to learners.